Motor Educability Between Students of Joalampe 47th State Elementary School and Puri Taman Sari Elementary School Makassar - Syahruddin, Syahruddin; Saleh, Muh. Sahib; Saleh, Muhammad Syahrul (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
This research is descriptive. This study aims to determine the comparison of the motor educability of students of SD Negeri 47 Joalampe with students of SD Puri Taman Sari Makassar. The population is all Grade V students of SD Negeri 47 Joalampe and SD Puri Taman Sari Makassar. The sample used was 50 students. The sampling technique was by random selection using a lottery (Simple Random Sampling). The data analysis technique used was descriptive analysis. The results of the study showed that; 1) the comparison of motor educability of students of SD Puri Taman Sari Makassar is better than the results of motor educability of students of SD Negeri 47 Joalampe.